Web Based Telecenter Training Management System at Yevern Region in Libya (WBTTMS) - Abokhwt, Azaden Mohamed Salem (2012)
In telecenters, the process of managing the training programs is still done manually therefore this study comes up with new website for ITU-UUM telecenter which help the telecenter management to manage the telecenter training programs easily where this study reduce the effort and time of managing the telecenter programs for the people. To develop such system, the general methodology has been used to develop the system, on the other hand. The entire study is hereby divided into to four main stages (1) requirement gathering, (2) prototype development, (3) prototype implementation and (4) usability testing. Questionnaire has been used as a usability technique for purpose of evaluating the system in terms of usefulness and easiness. The evaluation reveals that 72.6% of the participants indicated that the prototype usefulness which is high and agreed altitude.